Micro-grid Concept for Coordinated Control of Renewable Energy Power Plants and a Way to Integrate with Main Grid - Anuraj, U.; Yuvaraj, M.; Rajan, R.; Hameed, I.; Arunprakash, N.; Sajeeva, J.; Kiriparan, B.; Yaalini, B.; Thananjeyan, S.; Tharsika, T.; Ahilan, K.; Atputharajah, A. (IEEE, 2022)
Many research papers discussed the increasing fossil fuel cost. As the cost is increasing in the present scenario it is necessary to incorporate Renewable Energy (RE) technologies to take primary role in generating electricity. As a result of increasing the RE – based power generation and reducing the fossil fuel technologies to generate electric power has created real challenges in power system operations. It is the high time for the researchers to do detailed analysis to find possible ways to tackle the challenges in power system operations. In the past, power system preferred to have large inertia to keep up its operations especially during transient periods of a disturbance. The modernized systems with latest technologies and their speedy responses, could create inertia by properly coordinating the control of many, small, generating plants. Further the accurate prediction algorithms release the stress by giving advance information about the system. As it is a new direction of modernized control, it always starts with small system and then integrates with large system through a supervisory control loop. This is opening a new direction with the RE technologies to be incorporated through microgrid systems.
Keywords: Micro-grid; Coordinated control strategy; RE power plants; Islanded grid operations